The ClC-5 knockout mouse model of Dent's disease has renal hypercalciuria and increased bone turnover. - Silva, I; Cebotaru, V; Wang, H; Wang, X; Wang, S; Guo, G; Devuyst, O; Thakker, R; Guggino, W; Guggino, SE (2003)
Dent's disease is a nephrolithiasis disorder associated with hypercalciuria and low molecular weight proteinuria that is caused by mutations in the voltage-gated chloride channel ClC-5. Because the exact cause of hypercalciuria in this disease is unknown and could come from a renal, intestinal, or bone origin, we have investigated overall calcium handling in the ClC-5 knockout mouse (ClC-5 KO). On a high calcium diet, ClC-5 KO mice had elevated serum 1alpha,25-dihydroxyvitamin D3 (1alpha,25D3), alkaline phosphatase (AP), osteocalcin (OC), and urinary deoxypyridinoline (DPD), but serum parathyroid hormone (PTH), calcium, and intestinal calcium uptake was similar to that of wild-type (WT) mice. A 30-fold decrease in dietary calcium intake caused elevation of serum PTH and urinary cyclic adenosine monophosphate in ClC-5 KO mice and decreased the renal calcium excretion, which still remained 2-fold above that of WT mice. On this low calcium diet, both groups of mice had the same serum 1alpha,25D3, with similar increments in intestinal calcium absorption, serum AP, OC, and urinary DPD. These data indicate that the hypercalciuria in the ClC-5 KO mice on low and high calcium diets is of bone and renal origin and is not caused by increased intestinal calcium absorption, despite an elevated serum 1alpha,25D3. These mice data suggest that young patients with this disease may have a propensity for altered bone homeostasis that should be monitored clinically.